2023
DOI: 10.3389/frai.2022.963781
|View full text |Cite
|
Sign up to set email alerts
|

Frost prediction using machine learning and deep neural network models

Abstract: This study describes accurate, computationally efficient models that can be implemented for practical use in predicting frost events for point-scale agricultural applications. Frost damage in agriculture is a costly burden to farmers and global food security alike. Timely prediction of frost events is important to reduce the cost of agricultural frost damage and traditional numerical weather forecasts are often inaccurate at the field-scale in complex terrain. In this paper, we developed machine learning (ML) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…This explanation is consistent with findings of Talsma et al . (2023), who showed that a convolutional neural network predicted minimum temperature with much less warm bias that RF, especially for sparse data at the extrema. Forecasting of minimum temperature by RF and ANN was also studied by Eccel et al .…”
Section: Discussionmentioning
confidence: 99%
“…This explanation is consistent with findings of Talsma et al . (2023), who showed that a convolutional neural network predicted minimum temperature with much less warm bias that RF, especially for sparse data at the extrema. Forecasting of minimum temperature by RF and ANN was also studied by Eccel et al .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, to avoid unnecessary expenses, it is essential for farmers to accurately recognize when a frost episode poses an actual threat. In this context, access to precise meteorological data and frost risk forecasts assumes an invaluable role [23].…”
Section: A Frost Predictionmentioning
confidence: 99%
“…It has the capability of identifying unseen patterns, and complex interconnections in the data series. Machine learning models are capable of predicting nonlinear relationships with high accuracy 35 , 36 . Therefore, several (8) state-of-the-art machine learning models were utilized to predict the surface and 10 cm depth soil temperature.…”
Section: Study Area and Datasetmentioning
confidence: 99%